2019
DOI: 10.3748/wjg.v25.i33.4885
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to vinyl chloride and liver diseases

Abstract: Portal hypertension, liver fibrosis, and angiosarcoma of the liver (ASL) have been reported among workers exposed to vinyl chloride monomer (VCM) since the 1970s. In 2007, the International Agency for Research on Cancer established the association of VCM with hepatocellular carcinoma (HCC), though only on the basis of the few cases available. Thereafter, recent reports from the United States cohort and a European sub-cohort of vinyl chloride workers provided compelling evidence of a strong association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Moreover, to further research this interaction, other studies have recently investigated the association between exposure and other forms of liver cancer, such as hepatocellular carcinoma 62 . Their latest method has been the in vitro study of the genotoxicity assessment of vinyl chloride 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, to further research this interaction, other studies have recently investigated the association between exposure and other forms of liver cancer, such as hepatocellular carcinoma 62 . Their latest method has been the in vitro study of the genotoxicity assessment of vinyl chloride 63,64 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiologic studies have demonstrated that exposures to VOCs were associated with various forms of liver injury and dysfunction ranging from elevated liver enzyme levels to steatohepatitis and liver cancer. For instance, it is well-documented that exposure to vinyl chloride, a historic occupational VOC, was associated with steatohepatitis in rubber plant workers, with some workers exhibiting hemangiosarcoma, a rare form of cancer affecting liver sinusoidal cells (Cave, et al, 2010;Fedeli et al, 2019). Other studies focusing on petroleum and auto-industry workers demonstrated that workers who were occupationally exposed to VOCs such as gasoline and other aromatic hydrocarbons, had higher mean levels of liver test results (ALT, AST and ALP) as well as total and conjugated bilirubin, when compared to non-worker controls (Asefaw et al, 2020;Egbuonu and Nkwazema, 2015;Mohammadi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They are associated with carcinogenic properties, respiratory problems, and kidney diseases among workers in petroleum refineries, coke ovens, and aluminum production [3,7,8]. The release of hazardous substances from PICs is also thought to increase the risk of cancer and chronic diseases among people living in the neighborhood [1,2,9,10]. Many studies have shown that PAHs are produced by the incomplete combustion of organic materials, and can be metabolized as 1-hydroxypyrene (1-OHP) and excreted through the feces and urine [2,3,11].…”
Section: Introductionmentioning
confidence: 99%